The unfolding of neoliberalism in economics curricula and scholarships: Colombia as a case study - Efrén Danilo Ariza Ruiz; Nestor Garza (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2024)
We document and analyze the emergence and consolidation of neoliberalism in higher education in economics in Colombia. The research focuses on four interrelated categories through which the neoliberal ideology changed the scientific field of economics by replacing endogenously developed analytical traditions during the 1980s -1990s: 1) homogenization of curricula; 2) neoclassical mathematization; 3) use of textbooks; and 4) quantitative assessment (scientometrics) of academic quality. The results show how a generation of economists combined their networks of social capital and legitimacy from international academic connections, to simultaneously impose their worldview in academia, the public administration, and private sector. Our analyses highlight the transfer of the neoliberal values to the education field through the concepts of quality assessment and scientometrics, which institutionalized the exercise of power to discipline intellectual inquiries and scholarship.
Keywords: 330; Higher Education; Economists; Research Policy; Cultural Capital; Sociological Studies; Neoclassical Economics